Through the Students’ Lens: Photographic Methods for Research in Library Spaces - Bedi, Shailoo; Webb, Jenaya (Evidence Based Library and Information Practice, 2017)
Objective – As librarians and researchers, we are deeply curious about how our library users navigate and experience our library spaces. Although we have some data about users’ experiences and wayfinding strategies at our libraries, including anecdotal evidence, statistics, surveys, and focus group discussions, we lacked more in-depth information that reflected students’ real-time experiences as they move through our library spaces. Our objective is to address that gap by using photographic methods for studying library spaces.Methods – We present two studies conducted in two academic libraries that used participant-driven photo-elicitation (PDPE) methods. Described simply, photo-elicitation methods involve the use of photographs as discussion prompts in interviews. In both studies presented here, we asked participants to take photographs that reflected their experiences using and navigating our library spaces. We then met with participants for an interview using their photos as prompts to discuss their experiences.Results – Our analysis of students’ photos and interviews provided rich descriptions of student experiences in library spaces. This analysis resulted in new insights into the ways that students navigate the library as well as the ways that signage, furniture, technology, and artwork in the library can shape student experiences in library spaces. The results have proven productive in generating answers to our research questions and supporting practical improvements to our libraries. Additionally, when comparing the results from our two studies we identified the importance of detailed spatial references for understanding student experiences in library spaces, which has implications beyond our institutions.Conclusion – We found that photographic methods were very productive in helping us to understand library users’ experiences and supporting decision-making related to library spaces. In addition, engaging with students and hearing their interpretations and stories about the photographs they created enhanced our research understandings of student experiences and needs in new and unique ways.